Risk-sharing or risk-taking? Counterparty risk, incentives and margins - Bruno Biais; Florian Heider; Marie Hoerova (European Central Bank (ECB), 2012)
We analyze optimal hedging contracts and show that although hedging aims at sharing risk, it can lead to more risk-taking. News implying that a hedge is likely to be loss-making undermines the risk-prevention incentives of the protection seller. This incentive problem limits the capacity to share risks and generates endogenous counterparty risk. Optimal hedging can therefore lead to contagion from news about insured risks to the balance sheet of insurers. Such endogenous risk is more likely to materialize ex post when the ex ante probability of counterparty default is low. Variation margins emerge as an optimal mechanism to enhance risk-sharing capacity. Paradoxically, they can also induce more risk-taking. Initial margins address the market failure caused by unregulated trading of hedging contracts among protection sellers.
Keywords: G21; G22; D82; 330; Counterparty risk; derivatives; Insurance; margin requirements; Moral Hazard